Transforming Perception into Reality:: Establishing a Sustainable Tourism Framework in Bangladesh - Khan, Nahreen Islam; Roopam, Bushra Mariam (The Jahangirnagar Review, 2025)
This study explores tourists’ perceptions of sustainable tourism in Bangladesh, focusing on infrastructure, environmental management, community involvement, and sustainability awareness. Qualitative data from semi-structured interviews with domestic and international tourists who visited popular destinations, like Cox’s Bazar, the Sundarbans, and Srimangal, provides valuable insights. Thematic analysis identifies recurring themes and patterns in the data. By coding interview transcripts and categorizing codes into broader themes, the results are interpreted in the context of existing literature. The analysis reveals key themes, including tourists’ understanding of sustainability, their perceptions of tourism service quality, and the importance of local community involvement in tourism development. These findings shed light on the complexities of sustainable tourism in Bangladesh. It also offers a comprehensive analysis of their expectations, experiences, and recommendations for enhancement, yielding significant insights into the present condition of tourism in Bangladesh. It encompasses a thorough evaluation of current difficulties and prospective ideas for improving sustainable tourism. The conclusions and suggestions articulated in the study provide a basis for policymakers, tourism operators, and local communities to formulate more efficient sustainable tourism strategies. This study primarily examines tourists’ impressions; however, future research could broaden its reach by including viewpoints from additional stakeholders, such as local people, government entities, and private sector operators.